DOPPLER ASSESSMENT OF UTERO-PLACENTAL HEMODYNAMICS IN PREGNANT WOMEN WITH A HISTORY OF CORONAVIRUS DISEASE (COVID-19) - Ryzhyk, V. M.; Vdovenko, A. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2022)
The latest viral disease, which continues to spread today, is caused by a new coronavirus and poses a serious threat to public health around the world. To date, the effects of COVID-19 on pregnant women and infants have not been fully studied and remain a key area of interest. The study aimed to assess utero-placental circulation using Doppler ultrasound for pregnant women with a case history of coronavirus disease (COVID-19). A Doppler screening of utero-placental hemodynamics was performed for 156 pregnant women at 18-22 weeks. Of those, 75 pregnant women with a case history of coronavirus disease COVID-19 were in the first trimester of pregnancy. An abnormal blood flow was observed within the experimental group in 14 cases (18.6%). The analysis of spectrograms revealed the unevenness of the diastolic component with the formation of a dicrotic notch in the early diastolic phase in 5 cases (6.6%). In comparison with the control group, pregnant women with COVID-19 were twice as likely to have impaired blood flow in the uterine arteries. Uterine artery doppler measurement is really important for predicting adverse pregnancy outcomes and perinatal losses. Doppler indices of utero-placental blood flow have clinical value for pregnant women who have recovered from COVID-19.